PENINGKATAN HASIL PEMBELAJARAN SENI RUPA MEMBUAT CELENGAN MENGGUNAKAN MODEL PROJECT BASED LEARNING DI KELAS IV SDN 16 PADANG BESI KOTA PADANG - Julatifa, Suci; Mansurdin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was motivated by the low learning outcomes of students who thought that learning Fine Arts was just learning to draw and sing. This research aims to describe the improvement in learning outcomes for the fine art of making piggy banks from used goods using the project based learning (PjBL) model in class IV of SDN 16 Padang Besi, Padang City. This type of research is classroom action research (PTK) with a qualitative and quantitative approach. Implemented in 2 cycles, each cycle consists of 2 meetings. The subjects of this research were 27 students. The research results show: First, the teaching module aspect obtained an average of 83.33% (B) increasing in cycle II to 91.66% (SB). Second, the results of the implementation of cycle I in the teacher aspect obtained an average percentage of 87.50% (B), increasing in cycle II to 93.75% (SB). Third, the results of the implementation of cycle I in the student aspect obtained an average of 8361% (B), increasing in cycle II to 90.62% (SB). Fourth, student learning outcomes in cycle I obtained an average of 73.98% (C), increasing in cycle II to 83.61% (B). It can be concluded that the Project Based Learning (PjBL) model can improve learning outcomes for the fine art of making piggy banks from used goods for class IV students at SDN 16 Padang Besi, Padang City.